METODE UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY UNTUK MENENTUKAN FAKTOR TINGKAT PENERIMAAN PENGGUNAAN E-LEARNING - Ferry Susanto (Jurnal Informatika, 2019)
This study aims to identify factors - factors that affect the level of user acceptance of e-learning in STMIK Surya Intan Kotabumi by lecturers as users, teachers and content developers. This study uses a model approach Unified Theory of Acceptance and Use of Technology (UTAUT) and models - other models. Model UTAUT dimofikasi by adding some variables to refer to the study - previous research. Variables used include performance expectancy, social influence, facilitating conditions, self-efficacy, information quality, system quality, service quality, behavioral intention, actual use and moderator usia..Langkah-step analysis of factors - factors is making a questionnaire derived from the model UTAUT, alter the results of a questionnaire by the method of successive interval (MSI). Furthermore, analysis of data using Structural Equation Modeling with Partial Least Square (PLS-SEM). PLS The data were processed using the application smartPLS. The results showed that only four variables that affect directly the use of e-learning (actual use) by lecturers at STMIK Surya Intan Kotabumi. These variables include interest for the use of e-learning (behavioral intention),influence the ability of professors to the use of e-learning (self-efficacy), influence the quality of information provided e-learning (information quality), and quality of service (service quality).Keyword : E-Learning, UTAUT, MSI, PLS-SEM, SmartPLS